Enhanced dielectric loss induced by the doping of SiC in thick defective graphitic shells of Ni@C nanocapsules with ash-free coal as carbon source for broadband microwave absorption. (11th October 2017) - Li, Zhenxing; Ding, Xiaoli; Li, Fan; Liu, Xianguo; Zhang, Shihong; Long, Hongming
Abstract: The rapid development of microelectronic devices means increasing attention is being paid to the exploration of high-performance microwave absorption materials. Enhanced dielectric loss is an effective way of improving microwave absorption performance. Here, we report that Ni@C nanocapsules with ash-free carbon as a carbon source, functionalized by the doping of SiC in a thick defective graphitic shell, demonstrate enhanced dielectric losses at the gigahertz level, and energy transfer from permeability to permittivity at 14.24 GHz. Compared with Ni@C nanocapsules, which have ethanol as a carbon source, the same absorption band and absorption intensity can be obtained with a thinner absorber in the present Ni@C nanocapsules, and the frequency corresponding to maximum reflection loss exhibits a red shift for the same absorbing thickness. At 5.12 GHz, the maximum reflection loss value of the present Ni@C nanocapsules can reach −49.99 dB for a planar absorber with a thickness of 5.1 mm. Experimental results coupled with theoretical simulations reveal the electromagnetic losses of the present Ni@C nanocapsules originating from the core–shell interfacial polarization and dipole polarization of the doping of SiC in the defective graphitic shell.